Reproductive parameters of female Wistar rats treated with methylphenidate during development - Montagnini, Bruno Garcia; Silveira, Kennia Moura; Pierone, Bruna Caroline; Camim, Nathalia de Azevedo; Anselmo-Franci, Janete Aparecida; Paccola Mesquita, Suzana de Fatima; Inhasz Kiss, Ana Carolina [UNESP]; Cetcatto Gerardin, Daniela Cristina (Elsevier B.V., 2016)
Methylphenidate (MPH), a psychoactive agent that acts mainly by blocking the uptake of dopamine, is the main drug used to treat Attention Deficit Hyperactivity Disorder in children and adolescents. During development, important changes in brain architecture and plasticity occur, these changes, sensitive to exposure to stimulant drugs, are important in the control of GnRH secretion, influencing the release of sex hormones throughout the ovarian cycle. This study investigated the effects of repeated treatment with MPH during development on reproductive parameters of adult female rats. Wistar rats received MPH 2.5 mg/kg, MPH 5.0 mg/kg, or tap water (gavage) from postnatal day (PND) 21 to PND 60. From PND 75, one subgroup of females was selected for evaluation of estrous cycle, estradiol levels, weight of sexual organs, and histomorphological analysis of ovary follicles and uterus. In another subgroup, the sexual and maternal behaviors were evaluated at PND 90 and on lactational day 5, respectively. No significant alterations were observed in the MPH groups. This study demonstrated that repeated administration of MPH during the period corresponding to childhood to early adulthood does not interfere in the reproductive function of female rats in adulthood. (C) 2016 Elsevier Inc All rights reserved.
Keywords: Attention-deficit/hyperactivity disorder; Methylphenidate; Development; Female rat